Hubungan antara dukungan keluarga dengan Kualitas hidup pasien covid-19 - Swita Winarni; Wiyadi Wiyadi; Hesti Prawita Widiastuti (MNJ (Mahakam Nursing Journal), 2023)
Harapan Insan Sendawar Hospital is one of the referral hospitals that is trusted to treat Covid-19 patients. By 2020, there were 153 COVID-19 patients recorded in April-December who tested positive and were treated. This research used observational descriptive study by approaching cross sectional. The population in this study were patients who had been hospitalized in the Meranti ward of the HIS Hospital from August 2021 to January 2022. The sample was determined by using purposive sampling and the research samplers were 76 respondents. The statistical test used was chi square while the p value <0.05 is obtained, then the hypothesis Ha is accepted and H0 is rejected. The result of research was gained by using Kolmogorov Smirnov namely a p value of 0.004 which is smaller than the value of = 0.05 or (0.004 <0.05), so it means that there is a significant relationship between family support and the quality of life of Covid 19 patients. The results showed that dominant in the good category, namely 68 people (89.5%). It means that there is a significant relationship between family support and the quality of life of Covid 19 patients. Keywords: Family support, Quality of life, Covid-19 patients.